Acute responses of hepatic fat content to consuming fat, glucose and fructose alone and in combination in non-obese non-diabetic individuals with non-alcoholic fatty liver disease - Kovar, J; Dusilova, T; Sedivy, P; Bruha, R; Gottfriedova, H; Pavlikova, P; Pitha, J; Smid, V; Drobny, M; Dezortova, M; Hajek, M (Journal of physiology and pharmacology, 2021)
We have recently demonstrated that a high-fat load can induce immediate increase in hepatic fat content (HFC) and that such an effect can be modified differently by co-administration of fructose or glucose in healthy subjects. Therefore, we addressed the question how consumption of these nutrients affects changes in HFC in subjects with non-alcoholic fatty liver disease (NAFLD). Eight male non-obese non-diabetic patients with NAFLD underwent 6 experiments each lasting 8 hours: 1. fasting, 2. high-fat load (150 g of fat (dairy cream) at time 0), 3. glucose (three doses of 50 g at 0, 2, and 4 hours), 4. high-fat load with three doses of 50 g of glucose, 5. fructose (three doses of 50 g at 0, 2, and 4 hours), 6. high-fat load with three doses of 50 g of fructose. HFC was measured using magnetic resonance spectroscopy prior to meal administration and 3 and 6 hours later. Plasma triglycerides, non-esterified fatty acids, glucose and insulin were monitored throughout each experiment. HFC increased by 10.4 ± 6.9% six hours after a high-fat load and by 15.2 ± 12.5% after high-fat load with fructose. When co-administering glucose with fat, HFC rose only transiently to return to baseline at 6 hours. Importantly, NAFLD subjects accumulated almost five times more fat in their livers than healthy subjects with normal HFC. Consumption of a high-fat load results in fat accumulation in the liver of NAFLD patients. Fat accumulation after a fat load is diminished by glucose but not fructose co-administration.
Keywords: Liver; glukosa; játra; Triglycerides; fruktosa; Fatty Acids, Nonesterified; krevní glukóza; Magnetic Resonance Spectroscopy; lidé; magnetická rezonanční spektroskopie; Non-alcoholic Fatty Liver Disease; inzulin; mužské pohlaví; Insulin; nealkoholová steatóza jater; Fructose; Diet, High-Fat; dieta s vysokým obsahem tuků; Blood Glucose; Humans; triglyceridy; kyseliny mastné neesterifikované; Glucose; Male